Gestión administrativa y su incidencia en el presupuesto operativo del gobierno autónomo descentralizado municipal del Cantón Quevedo - año 2015. - Holguín Olvera, Rubén Emilio (2016)
The administration of the Administrative and Operational Management of the different departments of the Autonomous Municipal Decentralized Government of Cantón Quevedo represents the budgetary management to solve the administrative expenses demanded by the municipal entity, obviously that the economic unit allows the development of infrastructure and social works for The society that inhabits it. The study is oriented to investigate the administrative and operational situation for the proper use of the established budget, ensuring economic benefits that do not tax one hundred percent to the budget of the Autonomous Government Decentralized Municipal Cantón Quevedo. The present study includes the interpretation of the phenomena related to the administrative and operational procedures and policies that are the object of the investigation of the Autonomous Municipal Government of the Cantón of Quevedo, which has budgetary deficiency, in which the problem of research that defines the problems Derivatives.